2011
DOI: 10.1590/s0102-86502011000800003
|View full text |Cite
|
Sign up to set email alerts
|

Changes caused by hidrocephalus, induced by kaolin, in the corpus callosum of adult dogs

Abstract: PURPOSE:To analyze the ventricular enlargement and myelination of the corpus callosum in adult dogs after four and eight weeks of kaolin-induction of hydrocephalus. METHODS: 36 dogs were randomly divided into 3 groups: 1 -without hydrocephalus, 2 -kaolin-induction of hydrocephalus until the fourth week, and 3 -kaolin-induction of hydrocephalus until the eighth week. Ventricular ratios and volumes were calculated using magnetic resonance images, and myelination of the corpus callosum were histologically evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
(18 reference statements)
1
6
0
2
Order By: Relevance
“…5) is indicative of a remyelination attempt. The possibility of remyelination is in consonance with the finding of Cardoso et al [15] in a dog model of hydrocephalus at 8 weeks after induction. However, the possibility of a modulating role of species type on the timing of remyelination is manifested by these findings.…”
Section: Discussionsupporting
confidence: 90%
“…5) is indicative of a remyelination attempt. The possibility of remyelination is in consonance with the finding of Cardoso et al [15] in a dog model of hydrocephalus at 8 weeks after induction. However, the possibility of a modulating role of species type on the timing of remyelination is manifested by these findings.…”
Section: Discussionsupporting
confidence: 90%
“…However, it has been found to underestimate the degree of ventricular distension [ 44 ]. Other measurements estimating the relation between frontal horn diameter and brain parenchyma have been used on different levels and image planes in the dog brain using different imaging modalities [ 7 , 9 , 44 49 ]. Only one study found a significant difference between dogs with ventriculomegaly and hydrocephalus [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As was the case we observed in sheep, kaolin administration to dogs represents a serious challenge to the animals. In one study in which 50 mg/kg kaolin was administered into the cisterna magna, the mortality rate was 38% [32]. In any event, the negative publicity associated with the use of dogs in research in some locations discourages their use.…”
Section: Discussionmentioning
confidence: 99%